Seksinfo : facetten van de seksuele problematiek - Van Brederode, Paul N.; Werkgroep studium generale SEX'69; Schnabel, Paul; Rijksuniversiteit te Utrecht (RUU) (Utrecht : RUU, 1969)
Fonds Suzan Daniel (FSD)
Nederlands
Monografie